Clinical implications of SARS‐CoV‐2 cycle threshold values in solid organ transplant recipients. Issue 3 (31st October 2020) - Gaston, David C.; Malinis, Maricar; Osborn, Rebecca; Peaper, David R.; Landry, Marie; Juthani‐Mehta, Manisha; Azar, Marwan M.
Abstract: Detection of SARS‐CoV‐2 viral RNA by RT‐PCR assays is the primary diagnostic test for COVID‐19. Cycle threshold (CT ) values generated by some of these assays provide inversely proportional proxy measurements of viral load. The clinical implications of CT values are incompletely characterized, particularly in solid organ transplant (SOT) recipients. We conducted a retrospective chart review of 25 adult SOT recipients admitted to the Yale New Haven Health System between March 1 and May 15, 2020, analyzing 50 test results to investigate the clinical implications of SARS‐CoV‐2 CT values in this population. Initial CT values from upper respiratory tract samples were significantly higher in patients on tacrolimus, but were not associated with admission severity nor highest clinical acuity. Viral RNA was detected up to 38 days from symptom onset with a gradual increase in CT values over time. In five patients with serial testing, CT values <35.0 were detected >21 days after symptom onset in 4/5 and ≥27 days in 2/5, demonstrating prolonged RNA detection. These data describe SARS‐CoV‐2 viral dynamics in SOT patients and suggest that CT values may not be useful to predict COVID‐19 severity in SOT patients. SARS‐CoV‐2 CT values may be more useful in informing infection prevention measures. Abstract : Although SARS‐CoV‐2 polymerase chain reaction cycle threshold values at admission are not associated with clinical severity, detection of SARS‐CoV‐2 at cycle threshold levels consistent with culturable virus for a prolonged period after symptom onset may impact current infection prevention practices for immunocompromised patients.